Isolated paediatric orbital fractures: A case series at a major trauma center. (October 2021) - Harrison, P.; Green, A.; Chellappah, A.; Fan, K.
Abstract : Purpose: Paediatric orbital fractures are rare. The existing literature demonstrates wide variation in estimates of incidence, aetiology, management protocols and outcomes. Despite this, it is generally acknowledged that orbital fractures with entrapment of the extraocular muscles constitute a surgical emergency due to the potential for persistent diplopia secondary to muscle ischaemia and necrosis. Methods: This was a retrospective study, conducted to determine the characteristics and outcomes of management of orbital fractures amongst the paediatric population. It involved patients presenting to King's College Hospital, London between 2010-2020. Results: 20 patients with pure orbital fractures presented to our Unit in this period. The average age of the patients was 11 years with a male preponderance. The predominant aetiology was road traffic accidents, but in surgical patients aged 13 to 16 this was interpersonal violence. The most common fracture pattern involved the orbital floor and medial wall. 9 patients required surgical intervention due to diplopia caused by entrapment of extraocular muscles. 5 patients had nausea, vomiting or bradycardia associated with the occulocardiac reflex. Surgical intervention occurred within 24 - 48 hours of the patient sustaining their injury in 6 cases. Resorbable sheet was used to reconstruct the orbit. Resolution of diplopia occurred in 7 patients within 6 months. Length of follow up ranged from 1 to 18 months. Conclusions: Paediatric patients with orbital fractures should be assessed on the day of injury by a maxillofacial surgeon. Due to the risk of persistent diplopia, urgent surgical intervention in patients with entrapment of extraocular muscles should occur as soon as possible.